Anthropometric index and low back functional disability among college students physically inactive - Maia, Marianna de Freitas (2014)
The aim of the study was to identify the prevalence of obesity, coronary risk and low back disability (LBD) among university students physically inactive both genders. Participants were 98 college students, 54 women with 26± 6.9 years and 44 men with 24± 6.5 years old. The Roland Morris Questionnaire (RMQ) was used to assess the prevalence of LBD. The body mass index (BMI) and waist-hip ratio (WHR) were used in order to identify over weight and risk of coronary heart disease. In statistics, we applied the chi-square (x2) for the RMQ (p <0.05). The mean BMI 23.9 ±4.0 (women) and 24.7±3.5 (men) were classified as normal. As for coronary risk, ICQ average (0.75±0.53) indicated high risk women compared to men (0.82±0.42). The responses of RMQ showed no association with the answer yes, or no IFL prevailed in the sample. Thus, BMI classified as normal may explain the absence of IFL in the sample. However, WHR indicated for women at high risk for coronary disease, this finding may be associated with physical inactivity.